الفهم الصحيح للزهد وعلاقتة بالرزق - القهوجي، بشار محمد رضا (رابطة الأدب الحديث, 2016)
يخطئ الكثير من الناس عندما يظنون أن الزهد عبارة عن ترك ومجافاة أسباب الحياة، ولبس المرقع والخشن من الثياب، وسكنى المتهدم من الديار، وركوب الهزيل من الدواب والمراكب.. فيهجر الزاهد –بزعمهم -زينة الدنيا وطيباتها، ويشمر للعبادة والطاعة، فلا يلهينه شيء عن ذكر الله وشكره وعبادته، وكل ذلك غير صحيح، ويبتعد أشواطاً عن الفهم الصحيح للزهد وعلاقته بالرزق. فالزهد الحقيقي يقوم على أن يمتلك الفرد أسباب الحياة من المال والإمكانيات، ولكنه يجعلها وسيلة ليتبلغ بها إلى الآخرة، فتكون في يده أو في جيبه لا في قلبه، بمعنى أنه يملكها ويسيطر عليها، ولكنها ليست هدفه ومبتغاه، فالهدف مرضاة الله والغاية هو الآخرة.. فتكون ثقته بما عند الله أوثق مما في يده، مهما تجمعت لديه الأسباب والإمكانات.
A lot of people miss the proper meaning of the asceticism. Since they think that the Muslim has to leave and be shunned the causes of life if he wants to be close from God. Thus he has to wear patchy and coarse clothes, live in dilapidated homes, ride lean animals or old cars, etc. But in all cases, it was a big mistake in their thinking. The real asceticism based on that the Muslim has to have all keys and reasons of life, money and resources; but he has to keep them away from his heart, so that the money and resources shall be in his hand or in his pocket, not in his heart. In the sense that he own and control, but it's not his final goal and aim which is certainly to have the pleasure of God.
Keywords: العقيدة الإسلامية -- الزهد -- التصوف -- الفكر الصوفي -- الاخلاق الاسلامية -- الفكر الديني